Elucidation of the role of breathless, a Drosophila FGF receptor homolog, in tracheal cell migration. - Reichman-Fried, M.; Dickson, B.; Hafen, E.; Shilo, B.Z. (Genes & Development, 1994)
DFGF-R1 (breathless), a Drosophila FGF receptor homolog, is required for the migration of tracheal cells and the posterior midline glial cells during embryonic development. To define the role of this receptor in cell migration, we have monitored the biological effects of a deregulated receptor containing the extracellular and transmembrane regions of the torso dominant allele and the cytoplasmic domain of DFGF-R1. Ubiquitous expression of the chimeric receptor at the time of tracheal cell migration did not disrupt migration in wild-type embryos. However, induction of the chimeric receptor corrected the tracheal defects of breathless (btl) mutant embryos, allowing the tracheal cells to migrate along their normal tracts. This result indicates that the normal activity of DFGF-R1 in promoting cell migration does not require spatially restricted cues. Late inductions of the chimeric construct, after the normal initiation of tracheal migration, allowed the definition of a broad time window during which the external signals guiding migration persist and the tracheal cells retain the capacity to respond to these cues. Rescue of tracheal migration in btl mutant embryos by the chimeric construct provides a sensitive biological assay for the activity of other Drosophila receptor tyrosine kinases (RTKs). Deregulated receptors containing the cytoplasmic domains of DFGF-R2, DER, torso, and sevenless were all able to partially rescue the migration defects. Consistent with the notion that these RTKs share a common signaling pathway, constructs containing the activated downstream elements Dras1 and Draf were also able to rescue tracheal migration, demonstrating that these two proteins are key players in the DFGF-R1 signaling pathway.